Vascular flora and vegetation from Puerto Viejo wetland - La Torre, María I. (2009)
The present paper is the first list of vascular flora from the Puerto Viejo wetland, Cañete, Lima. A total of 32 species of vascular plants, grouped in 28 genera and 15 families were registered between March 2003 and July 2009. The Magnoliopsidae (Dicotyledoneae) was the dominant group with 20 taxa. The 34% of the taxa (11 species) are considered as introduced species.